RESPOMS PERTUMBUHAN DAN PRODUKSI SAAWI (Brassica Juncea. L) TERHADAP INTERVAL PENYIRAMAN DAN KONSENTRASILARUTAN PUPUK NPK SECARA HIDROPONIK - Marnangon Alfa Tambunan; Asil Barus; Jasmani Ginting (Jurnal Agroekoteknologi, 2013)
The aimed of this reaserch was to determine the flush interval and consentration of NPK fertilizer which is suitable to the growth and production of mustard (Brassica juncea L.) This research was conducted at green house’s Agricultur faculty University of Sumatera Utara, Medan with a height of 25 metre sea level rise on Februari until April 2012. This research was conducted by factorial randomized block design with two factors such as flush interval (1,2,3 in a day) and NPK fertilizer 0, 2.5, 5, 7. 5, 10 (g/l water). The parameters observed were plant height, the number of leaf, leaf area, the scale of leaf chlorophyll , the weight biomass of plant, The fresh weight of selling, the weight of roots, the root’s length and the harvest indeks. The result of the observations showed that the flush interval had ureal effect to all of the parameters except the root’s weight, while the NPK fertilizer had a real effect to all of the parameters.